Development And Validation Of A Questionnaire Assessing The Knowledge, Attitudes And Practices Of Young Adults In Malaysia Towards Sugar Sweetened Beverages - Nur Islami Mohd Fahmi Teng; Siti Zarifah Abd Latif; Norsham Juliana Nordin (Pharmascope Publications, 2024)
Indexed by SCOPUS